1997
DOI: 10.4141/s95-075
|View full text |Cite
|
Sign up to set email alerts
|

Utilisation de l'engrais azoté marqué au 15N par le maïs selon les modes d'application et les doses d'azote

Abstract: The main objective of this study was to compare the recovery of 15N-labelled fertilizer by different methods of N application and N rates. Field experiments were carried out for 3 yr at Saint-Hyacinthe (Saint-Damase, Du Contour, Sainte-Rosalie soils) and at Saint-Lambert, Lévis (Le Bras soil). Grain corn (cv. Pride K228, 2700 CHU) and silage corn (cv. Hyland 3251, 2300 CHU) were grown at Saint-Hyacinthe and Saint-Lambert, respectively. In 1988 and 1989, field trials were arranged in a randomized complete bloc … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
2
3

Year Published

2001
2001
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 19 publications
2
7
2
3
Order By: Relevance
“…These values are in the middle of the range of those reported by Tran and Giroux (1991) and Beauchemin et al (1990) for potato soils, slightly lower than those reported by Tran et al (1997) for corn soils, but larger than those reported by Ziadi et al (1999) from meadow soils in the Temiscaming area.…”
Section: Residual Response Of Sweet Corncontrasting
confidence: 48%
See 1 more Smart Citation
“…These values are in the middle of the range of those reported by Tran and Giroux (1991) and Beauchemin et al (1990) for potato soils, slightly lower than those reported by Tran et al (1997) for corn soils, but larger than those reported by Ziadi et al (1999) from meadow soils in the Temiscaming area.…”
Section: Residual Response Of Sweet Corncontrasting
confidence: 48%
“…Moisture content was calculated from weight loss after oven-drying to a constant weight at 105°C. Soil was also analysed for 0.01 M CaCl 2 --extractable NH 4 + , NO 3 -, and Mehlich-3 extractable P, K, Ca, Mg (Tran and Simard 1993). The NO 3 -content was determined by ion chromatography on a Dionex 4000i chromatograph (Dionex Corp., Sunnyvale, CA).…”
Section: Soil Analysismentioning
confidence: 99%
“…Les cumuls des UTM ont e´te´supe´rieurs ou e´gaux a`la normale de 3020 UTM au cours de toutes les anne´es expe´rimentales (Tableau 2) a`l'exception de l'anne´e 2000 ou`le cumul des UTM n'a e´te´que de 2723 UTM, un cumul infe´rieur de 10% par rapport a`la normale (Bootsma et al 1999 (Tran et al 1997;Ziadi et al 2007). Le rendement annuel moyen le plus faible (6.52 Mg ha…”
Section: Ré Sultats Et Discussionunclassified
“…Le sommaire des donne´es climatiques de Saint-Hubert (Tableau 2) indique des pre´cipitations de 206 mm au cours du mois de juillet en 2004 comparativement a`la normale de 98 mm. Cette pluviome´trie plus abondante que la normale coincidait avec la croissance rapide du maı¨s (Tran et al 1997), croissance qui se traduit par des besoins en eau qui exce`dent ge´ne´ralement la pluviome´-trie naturelle et par des besoins importants en azote afin d'assurer un bon rendement en grains (Tran et al 1997). Dans l'e´tude de Ziadi et al (2007), les pre´cipitations enregistre´es en juillet 2004 n'ont toutefois e´te´que de 114 mm (Environnement Canada 2010).…”
Section: Effet De La Fertilisation Azoté E Sur Les Rendements Des Culunclassified
See 1 more Smart Citation